Mental Health Status Assessment in Polycystic Ovarian Syndrome Infertility Patients： A Pilot Study - 李赛姣;周丹妮;李维;杨菁 (Current medical science, 2017)
Polycystic ovary syndrome（PCOS） is a major endocrine disorder afflicting women of reproductive age. Women with PCOS are more likely to suffer from mental health disturbances than healthy women. The ＂infertility＂ suffered by PCOS patients would also lead to mental health disturbances. Symptom Checklist 90（SCL-90） and questionnaire which includes patients＇ socio-economic and demographic data were used to assess the mental health status of PCOS（n=103） and non-PCOS（n=110） infertile patients. Logistic regression analysis and t-tests were used for comparative analysis. The data demonstrated that scores of depression, interpersonal sensitivity, obsessive-compulsive, and hostility symptoms in PCOS infertile patients were significantly higher than those in the non-PCOS infertile patients（P〈0.05）. Logistic regression analysis revealed that acne had negative effect on mental health status（P〈0.05）. Secondary infertile PCOS patients were more easily to suffer from somatization, interpersonal sensitivity, obsessive-compulsive, anxiety, hostility and paranoid ideation symptoms than the primary infertile PCOS patients（P〈0.05）. The results suggested that the PCOS patients especially the secondary infertile PCOS patients had obvious mental health disturbances. The acne might play an importance role in the occurrence of mental health disturbances in PCOS patients. PCOS related symptoms may be risk factors of mental health status in PCOS patients with infertility. More attention should be paid to the PCOS infertile patients, and mental health therapy should be considered if necessary.